2017
DOI: 10.3389/fneur.2017.00492
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Traumatic Brain Injuries in Baseball and Softball: A Framework for Prevention

Abstract: BackgroundTraumatic brain injuries (TBIs) are an important public health challenge. The classification of baseball and softball as low contact sports and their association with extremity injuries cause individuals to overlook the risk of TBI in baseball and softball.PurposeTo summarize our knowledge of the epidemiology and risk factors of TBIs associated with baseball and softball with an aim to better design and implement preventive strategies.MethodsA search algorithm containing keywords that were synonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
(198 reference statements)
0
12
0
Order By: Relevance
“…The majority of the current literature focuses on the importance of protective equipment to prevent concussions. [11][12][13] For example, 1 study stated that head protective gears have decreased sports-related head injuries, whereas their protective effects on concussions are less clear. 4 However, we found that traumatic facial injuries such as facial contusions, lacerations, and fractures, are more common than concussions amongst youth baseball players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the current literature focuses on the importance of protective equipment to prevent concussions. [11][12][13] For example, 1 study stated that head protective gears have decreased sports-related head injuries, whereas their protective effects on concussions are less clear. 4 However, we found that traumatic facial injuries such as facial contusions, lacerations, and fractures, are more common than concussions amongst youth baseball players.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this investigation is to examine the type and frequency of baseball-related craniofacial injuries among the pediatric baseball athletes. The majority of the current literature focuses on the importance of protective equipment to prevent concussions 11–13 . For example, 1 study stated that head protective gears have decreased sports-related head injuries, whereas their protective effects on concussions are less clear 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of impact to the front of the head have also been greatly discussed as the most frequent area of impact in many sports (Crisco et al, 2010; Comstock et al, 2014). For example, there are a considerable number of reports on projectile impact via a bat or ball to the front of the head in baseball and softball catchers (Beyer et al, 2012; Cusimano et al, 2017). This 2 nd Skull study showed reduced impact at the front of the head for both baseball by 44% and softball by 51%, which exhibits the promising effect of the 2 nd Skull caps in confronting this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Other sports that can involve head impact and can be related to TBI's are: ball games -basketball (Covassin et al, 2017), volleyball (Baugh et al, 2017), baseball and softball (Cusimano, Zhu, 2017), floorball (Pasanen et al, 2017), lacrosse (Barber Foss et al, 2017), hurling (O'Sullivan et al, 2017); contact sports -judo (Čierna et al, 2017), wrestling (Kroshus et al, 2017); othersgymnastics , horse racing (O'Connor et al, 2017).…”
Section: Incidence Of Src In Various Sport Disciplinesmentioning
confidence: 99%